VKORC1 Haplotypes in patients treated with warfarin - Beshna, E; Teh , Lay Kek; Ngow, Harris Abdullah; Harun, Roslan; Salleh, Mohd Zaki (2010)
Background: Warfarin has very narrow therapeutic windows and large individual variability. Genetic variants encoding VKORC1 gene has resulted in altered sensitivity to warfarin or warfarin resistance. Nine haplotypes (H1-H9) of VKORC1 had been categorized with reference to 10 SNPs (Gen Bank accession number AY587020). Objective: To determine the haplotypes frequencies of VKORC1 gene among the patients prescribed warfarin and to correlate the dose, INR and bleeding with haplotypes. Method: A total of 158 patients prescribed warfarin and met the inclusion criteria were recruited after informed consent. Five ml of blood was drawn from each patient and DNA was extracted for genotyping of VKORC1 variants. Two steps PCR methods were developed to identify all the 10 SNPs. The optimized method was validated by direct sequencing. Result: Twenty-six (26) haplotypes were inferred from 10 common SNPs. Only four haplotypes have frequency more than 2.5%. The VKORC1 haplotypes with the highest frequency was H1 (72.5%) followed by H6 (3.8%), H7 (7.3%) and H10 (2.5%). Two haplotypes (H1 and H10) were associated with a low warfarin dose requirement (2.9 and 2.63 mg per day; p<0.01)) while H6 and H7 were associated with high dose requirement (4.55 and 4.83 mg per day; p<0.01). The average INR was approximately 2.4 and did not differ significantly among the patients classified according to VKORC1 haplotype combination (P value=0.196). The multiple regression analysis (Enter method) indicated that VKORC1 accounted for 24.8 % the variation in warfarin dose. Conclusion: VKORC1 haplotype provided a good correlation for different warfarin dose requirements. Genotyping of patients before warfarin is thus useful to predict more accurately dose required. Corresponding author: M. Z. Salleh, Head, Pharmacogenomics Centre, Faculty of Pharmacy, Universiti Teknologi MARA Malaysia. Acknowledgement: This study was supported by kecermerlangan’s UiTM.